Pendampingan Pembuatan Mural Untuk Revitalisasi Lingkungan Pasca Pandemi - Soetam Rizky Wicaksono; Didit Prasetyo Nugroho; Rudy Setiawan (Indonesia Bergerak : Jurnal Hasil Kegiatan Pengabdian Masyarakat, 2024)
Rumah Belajar Aqiel (RBA) located in Lowokwaru, Malang Municipality, East Java, submitted a proposal to create murals on the walls of their building with the assumption of raising awareness about cultural insights for their students as well as being an encouragement for the surrounding community, especially during post-pandemic conditions that resulted in many surrounding residents losing and reducing income. The proposal was then welcomed by the Visual Communication Design  study program, Faculty of Technology and Design, Universitas Ma Chung, Malang, East Java, by sending a team from the lecturers and assistance from related students. The steps carried out in this service activity consist of three stages, namely: (1) brainstorming with the study room, (2) the initial sketching and design process for the mural, and (3) the process of making murals in collaboration with students as well as the implementation of MBKM. Furthermore, the mural painting process was carried out by involving students within 2 weeks, because the work process could not be done immediately at once. There are several stages such as preliminary sketches, sketch supervision and painting. In the mural drawn there are elements of archipelago batik, floral doodles and also classic type fonts so that the design can last a long time. The results of the implementation of this community service have succeeded in achieving the initial goals that have been set and activities in accordance with the expected targets.